FACTORS INFLUENCING EXPANSION OF COMMERCIAL PROPERTY IN KENYA: A CASE OF KERUGOYA TOWN, KIRINYAGA COUNTY - LUKETERO, DR. STEPHEN; KARIMI, JOY (IJRDO - Journal of Applied Management Science, 2019)
This study is on factors that influence expansion of commercial property in Kerugoya town, Kirinyaga county,Kenya. Four study questions guided this study. Literature review focused on expansion of commercial property globally, in Kenya and Africa at large. The study focused on the factors that influence expansion of commercial property which include demographic characteristics, interest rates,market demand and Gross domestic product(GDP). The study used the descriptive survey design. The target population for the study was 112 comprising 42 investors/developers, 30 financial consultants, 10 government departments and 30 property consultants in Kirinyaga County. A sample of 88 respondents was determined based on Yamane formula 1967. Piloting was done on 5 respondents from Kirinyaga County more so the ones who would not be used in the final study. Based on the findings the following conclusions were made: Demographic characteristics, market demand, interest rates and GDP were major determinants of commercial property investment in Kerugoya town.GDP growth contributed the most to the growth in commercial property, followed by market demand, demographic characteristics then interest rates. Hence these four factors i.e. demographic characteristics, interest rates, market demand and GDP had a statistically significant positive influence on investment of commercial property. It was also found that policy measures geared toward improving the economic growth and curbing rising inflation rates and interest rates should be undertaken as they increased the investment levels.The researcher also recommends the following: That future development of commercial properties in Kerugoya should be planned strategically bearing in mind that their development affects the economy of the county. In order for Kenya to bridge the gap between demand for residential housing units and supply, Kenyan developers, real estate firms, the government and all other key stakeholders involved in real estate market, should benchmark to obtain best practices and strategies in order to alleviate or ease the problem of inadequate housing.